A Descriptive Cross-Sectional Study on Clinical Profile and Outcome of Delirium in the Mechanically Ventilated Patients in the Semi-Closed Intensive Care Unit - Niraj Kumar Keyal; Jeetendra Kumar Mishra; Achutanand Lal Karn; Mohammed Islam Mansuri; Nitesh Kumar Sah; Sweta Yadav (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Delirium in mechanically ventilated patients is associated with a poor outcome. Delirium in mechanically ventilated patients is associated with a poor outcome, including increased length of stay, frequent medical complications, increased cost of care, and mortality. MATERIAL AND METHODS This prospective study was done in 67 patients of age ≥18 years who underwent mechanical ventilation for more than 24 hours in a level three intensive care unit of tertiary care hospital for one year. The ethical approval from the Institutional Review Committee was obtained before enrolment in this study The whole sampling method was used in our study. The Confusion Assessment Method-ICU and Richmond Agitation Sedation Scale were used to diagnose and motor subtype delirium, respectively, along with a checklist to assess risk factors. All data was transferred to the excel sheet and transferred to a statistical package for the social sciences-16. The risk factors were analyzed using binary logistic regression. RESULTS Of the 67 ICU admissions, 34 (38.4%) developed delirium. Mixed delirium was the most common motor subtype 36 (53.73%). The mean duration of delirium was 5.41±4.62 days.Hypoxemia, acute respiratory failure, and history of alcohol intake were identiﬁed as risk factors for delirium. Delirious patients had a longer length of stay in the ICU (11.8 ±8.1 vs 7.4±7.7 days) and duration of mechanical ventilation (5.1 ± 2.0 vs 2.5±1.6), with no impact on mortality, reintubation and unplanned extubation. CONCLUSION Hypoxemia, acute respiratory failure, and history of alcohol intake were identiﬁed as the risk factor for mortality in mechanically ventilated delirious patients that should be identiﬁed early to prevent complications such as longer length of stay and duration of mechanical ventilation in the semi-closed intensive care unit.